Silicon-Based Multilayer Waveguides for Integrated Photonic Devices from the Near to Mid Infrared - Iñaki López García; Mario Siciliani de Cumis; Davide Mazzotti; Iacopo Galli; Pablo Cancio Pastor; Paolo De Natale (Applied Sciences, 2021)
Advancements in spectroscopy, quantum optics, communication, and sensing require new classes of integrated photonic devices to host a wide range of non-linear optical processes involving wavelengths from the visible to the infrared. In this framework, waveguide (WG) structures designed with innovative geometry and materials can play a key role. We report both finite element modeling and experimental characterization of silicon nitride multilayer WGs from the visible to the mid-infrared spectral regions. The simulations evaluated optical behavior and mechanical stress as a function of number of WG layers and photonic structure dimensions. WGs were optimized for waveguiding at 1550 nm and 2640 nm. Experimental characterization focused on optical behavior and coupling losses from 532 nm to 2640 nm. Measured losses in WGs indicate a quasi-perfect waveguiding behavior in the IR range (with losses below 6 dB), with a relevant increase (up to 20 dB) in the visible range.